(Un)Dressing Children in the Lachish Reliefs: Questions of Gender, Status, and Ethnicity - Garroway, Kristine Henriksen (Near Eastern archaeology, 2020)
The Lachish reliefs were once part of Room XXXVI in Sennacherib’s Southwest Palace at Nineveh. R. D. Barnett made the claim that the Lachish reliefs represented an actual event, the siege and destruction of Lachish by Sennacherib in 701 BCE, and was not some stock depiction of the defeat of an enemy city, an assertion that David Ussishkin (2014) has verified. Monumental palace reliefs functioned in a variety of ways, and these reliefs in particular were meant as royal propaganda. Those entering Sennacherib’s palace would see that to resist the power of the Assyrian army was futile (Uehlinger 2003). Since few people could read, it was important that the actions shown on the wall monuments were self-explanatory, and “the participants and location easily recognizable” (Franklin 2001: 261).1 It follows then that the depictions of the people on the reliefs also portray a general picture of the parties involved (Uehlinger 2003: 263).